Hegemonic Ideology in Buruan Novel: A Post-colonial Study - Kartini, Ni Nyoman; Suarka, I Nyoman; Cika, I Wayan; Putra, Ida Bagus Rai (e-Journal of Linguistics, 2021)
This study aims at finding the ideology of hegemony in the novel Buruan based on post-colonialism studies. There are three elements of post-colonialism, namely hegemony, mimicry and hybridity. In this study, it focuses on the hegemony element because it reflects the hegemonic party and the hegemonic party. The method used in this research is the interview method and the literature method through the recording technique and note-taking technique. The results of the analysis were carried out by analytic descriptive with interpretation method and hermeneutic approach. The results showed that the perpetrators of hegemony in the novel Buruan were Japanese soldiers as invaders of the Indonesian people and skipper of the Misbah boat. Both of these actors treat women as oppressed parties from sexual behaviour and violence. This resulted in a hegemonic ideology that women as a subordinate group and victims of oppression from the attitude of male domination as a powerful group.